The Effect of Elderly Exercise on Independence in Performing Daily Activities and Reducing Blood Pressure in Elderly in the Working Area of Riaraja Community Health Center - Zulkifli; Yuly Peristiowati; Prima Dewi Kusumawati (Universitas STRADA Indonesia, 2025)
An increase in blood pressure will give continuing symptoms to a target organ in the body, lack of activity causes the heart to become untrained, blood vessels become stiff, blood circulation does not flow smoothly, in cases of hypertension the highest in Indonesia is 39.6% and in NTT it is 30.8%. One of the factors that influences hypertension is physical activity. Lack of physical activity can increase the risk of hypertension. The purpose of this study was to determine the effect of elderly gymnastics on independence in carrying out daily activities and reducing blood pressure in the elderly with hypertension. This type of research is Quasi Experimental with a one group pre test-post test design with a population of 146 and a sample of 34 people was taken using a non-probability sampling technique with a Purposive sampling type.